Answer:
coinciding
Step-by-step explanation:
If you divide the second equation by 3, you get the first equation. They describe the same line, so the lines are <em>coinciding</em>.
V=2.28943
I am not sure though
Answer:
2291,94 mph
Step-by-step explanation:
To solve this we need to consider the distance 2.39x10^5 miles as the distance between the center of the earth and the center of the moon, if not we would need to know the radius of the earth and the moon.
If the distance is 2.39x10^5 miles, the orbit is = 2.Pi.(2.39x10^5) miles=1501681.288miles
It takes 27.3 days, that are, 27.3*24= 655.2hours
1501681.288miles/655.2hours= 2291.94 mph
Answer:
Ok, we have a system of equations:
6*x + 3*y = 6*x*y
2*x + 4*y = 5*x*y
First, we want to isolate one of the variables,
As we have almost the same expression (x*y) in the right side of both equations, we can see the quotient between the two equations:
(6*x + 3*y)/(2*x + 4*y) = 6/5
now we isolate one off the variables:
6*x + 3*y = (6/5)*(2*x + 4*y) = (12/5)*x + (24/5)*y
x*(6 - 12/5) = y*(24/5 - 3)
x = y*(24/5 - 3)/(6 - 12/5) = 0.5*y
Now we can replace it in the first equation:
6*x + 3*y = 6*x*y
6*(0.5*y) + 3*y = 6*(0.5*y)*y
3*y + 3*y = 3*y^2
3*y^2 - 6*y = 0
Now we can find the solutions of that quadratic equation as:
![y = \frac{6 +- \sqrt{(-6)^2 - 4*3*0} }{2*3} = \frac{6 +- 6}{6}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B6%20%2B-%20%5Csqrt%7B%28-6%29%5E2%20-%204%2A3%2A0%7D%20%7D%7B2%2A3%7D%20%3D%20%5Cfrac%7B6%20%2B-%206%7D%7B6%7D)
So we have two solutions
y = 0
y = 2.
Suppose that we select the solution y = 0
Then, using one of the equations we can find the value of x:
2*x + 4*0 = 5*x*0
2*x = 0
x = 0
(0, 0) is a solution
if we select the other solution, y = 2.
2*x + 4*2 = 5*x*2
2*x + 8 = 10*x
8 = (10 - 2)*x = 8x
x = 1.
(1, 2) is other solution
Answer:
ΔMLN - ΔΡQO
Step-by-step explanation:
Therefore,due to the correct pattern ΔMLN - ΔΡQO is correct.